Laryngomalacia in Patients With Craniosynostosis. (August 2018) - Mathews, Fasil; Shaffer, Amber D.; Georg, Matthew W.; Ford, Matthew D.; Jabbour, Noel; Simons, Jeffrey P.
Objective: To characterize differences in the clinical presentation and treatment outcomes of laryngomalacia in patients with and without craniosynostosis. Methods: A retrospective cohort study was performed comparing all patients with concomitant laryngomalacia and craniosynostosis seen at a tertiary care children's hospital between 2000 and 2016 with a control group of patients with isolated laryngomalacia. Thirty-two patients with craniosynostosis (59% male) and 68 control patients (56% male) were included. There were no significant differences in age of diagnosis or incidence of prematurity. Symptom presentation, disease severity, swallowing function, comorbidities, treatment modalities, and outcomes were examined using logistic regression. Results: Patients with craniosynostosis had increased odds of presenting with stertor (odds ratio [OR] = 3.41, P = .022), increased work of breathing (OR = 18.8, P = .007), obstructive sleep apnea (OR = 8.48, P = .003), dysphagia (OR = 3.40, P = .008), and aspiration (OR = 40.2, P < .001) and decreased odds of presenting with stridor (OR = 0.0804, P < .001) compared with controls. Patients with craniosynostosis had increased odds of severe laryngomalacia (OR = 5.00, P = .031) and other airway anomalies such as tracheomalacia (OR = 5.73, P = .004), bronchomalacia (OR = 15.5, P = .013), and subglottic stenosis (OR = 2.75, P = .028). Treatment of patients with craniosynostosis was more likely to include tracheostomy (OR = 24.8, P < .001) and gastrostomy tube (OR = 88.4, P < .001). There were no significant differences in rates of supraglottoplasty. Conclusion: Clinical presentations, comorbidities, and treatments of laryngomalacia are significantly different in the context of craniosynostosis.